Pengaruh Sumber Daya Finansial, Aset Tidak Berwujud dan Keunggulan Bersaing yang Berimplikasi Terhadap Kinerja Usaha Mikro, Kecil dan Menengah di Lombok NTB - Ahmad Fauzi; Budi Suharjo; Muhammad Syamsun (Institut Pertanian Bogor, 2016)
The research analyzes the financial resources, intangible assets (innovation capital, human capital, and customer capital), competitive advantage and financial performance, also analyzing its effect and analyzing business feasibility from the point view of Net Present Value (NPV), Profitability Index (PI), Payback Period (PP) and Internal Rate of Return (IRR) on cow commodities, corn and seaweed (PIJAR). The method used is qualitative and quantitative, the respondent are choose by purposive sampling with the criteria of SME which conduct their business on cow commodities, corn and seaweed at Lombok NTB Region. This research is using the Partial Least Square (PLS) analysis which is a statistical method on varian basis. The research results obtained by the Financial Resource Capacity has well sufficient capacity of (3.29), Intangible Asset have well sufficient capacity of (3.86), well good for Competitive Strategy Excellence Cost of (3.92) and quite good Financial Performance. The influence among variables on the seaweed commodities : (1) Financial Resource does not affect the financial performance and price competitive competition, so the financial resources capacity is well good, although its not yet able to contribute on the financial performance; (2) Innovation capital affect on financial performances but do not affect on competitive strategy; human capital affect on the financial performance and competitive strategy; customer capital affect on the financial performance and competitive strategy; and (3) The business feasibility for PIJAR commodities are very well based on the view point of NPV, PP, PI and IRR.